Determination of Dopamine and Ascorbic Acid in Hypoxanthine System with Mercury Film Electrode Acid - Lian, Kaoqi; Niu, Lingmei; Kang, Weijun; Yang, Jintao (Asian Journal of Chemistry, 2010)
In this article, based on the analyses of former research (determination of dopamine in hypoxanthine system with glassy carbon mercury film electrode). The electrocatalytic oxidation for both dopamine and ascorbic acid in this system were also studied and the interference of ascorbic acid and dopamine in different pH values was discussed in detail. It indicated that at pH 1.81 buffer solution, the reduction peak of dopamine was almost unchanged when ascorbic acid coexisted. The reduction peak current of dopamine was proportional to its concentration in the range of 1.5 × 10-5-5.6 × 10-4 mol L-1 and the detect limit could reach 2 × 10-6 mol L-1. The oxidation peak current of ascorbic acid was linear with its concentration from 5 × 10-5-2.4 × 10-3 mol L-1. Detect limit of it reached 8 × 10-6 mol L-1. At pH 4.10 buffer solution, the oxidation peak of dopamine could be separated from that of ascorbic acid about 200 mV and the presence of dopamine had little effect on the oxidation peak of ascorbic acid. The method could obtain better result when it applied to the determination dopamine and ascorbic acid in medicament sample and synthetic sample.